Revolutionizing romance : interracial couples in contemporary Cuba - Fernandez, Nadine T., 1964- (Rutgers University Press, 2010)
Scholars have long heralded mestizaje, or race mixing, as the essence of the Cuban nation. Revolutionizing Romance is an account of the continuing significance of race in Cuba as it is experienced in interracial relationships. This ethnography tracks young couples as they move in a world fraught with shifting connections of class, race, and culture that are reflected in space, racialized language, and media representations of blackness, whiteness, and mixedness. Nadine T. Fernandez offers a rare insider's view of the country's transformations during the post-Soviet era.
Keywords: Interracial dating -- Cuba.; Interracial marriage -- Cuba.; Multiracial people -- Cuba.; Cuba -- Race relations.; Amours interraciaux -- Cuba.; Mariage interracial -- Cuba.; Cuba -- Relations raciales.; SOCIAL SCIENCE -- Sociology -- Marriage & Family.; SOCIAL SCIENCE -- Ethnic Studies -- Hispanic American Studies.; Interracial dating; Interracial marriage; Race relations; Multiracial people; Cuba; Electronic books.